Pengelolaan Limbah Rumah Tangga menjadi Eco-Enzyme melalui Proses Fermentasi - Indriyani; Tafzi, Fitry; Afdal, M.; Ulyarti; Lisani (WIDA Publishing, 2024)
Forum Indonesia Muda (FIM) is an independent forum consisting of young people from various backgrounds, universities, and youth movements from all over Indonesia, with the aim of building the nation through a spirit of collective contribution. With the diverse backgrounds of its members, each individual has their own role, leading FIM Jambi to have several divisions to channel the youth roles effectively. Organic waste is material that is discarded but still has potential for reuse, especially fruit and vegetable peels that can be processed into liquid and solid products beneficial to the environment. This liquid is known as eco-enzyme, which is highly beneficial for health, the environment, and agriculture. This activity aims to reduce the amount of fruit and vegetable peel waste. The community service activity is divided into four stages of implementation, namely: the survey stage, the socialization stage, the technical training stage, and the mentoring stage. The results of this activity are expected to generate a significant positive impact on waste management and environmental sustainability, particularly for FIM as youth who play a role in environmental preservation. This activity provides a solution that can be widely applied in the community to create a cleaner and healthier environment.